2018
DOI: 10.1186/s12879-018-3000-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of dengue IgG antibodies in symptomatic and asymptomatic individuals three years after an outbreak in Zhejiang Province, China

Abstract: BackgroundCross-reacting antibodies enhanced dengue infection in humans and antibody dependent enhancement (ADE) have been proposed as early mechanisms underlying DHF/DSS. However, the duration of dengue IgG antibodies in the body as well as factors associated with said duration remain unclear.MethodsBlood samples from 59 dengue symptomatic persons and 48 asymptomatic individuals were collected. Study participant demographic information (including age in 2009, gender, and place of residence) were also collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…In the present study, waning of antibody response was observed in 4.3% of children. A similar phenomenon has been observed in studies conducted in Taiwan and China [29, 30]. The study from China reported that the IgG prevalence was higher in symptomatic subjects compared to asymptomatic individuals [30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, waning of antibody response was observed in 4.3% of children. A similar phenomenon has been observed in studies conducted in Taiwan and China [29, 30]. The study from China reported that the IgG prevalence was higher in symptomatic subjects compared to asymptomatic individuals [30].…”
Section: Discussionsupporting
confidence: 82%
“…A similar phenomenon has been observed in studies conducted in Taiwan and China [29, 30]. The study from China reported that the IgG prevalence was higher in symptomatic subjects compared to asymptomatic individuals [30]. It is also possible that the subjects with antibody response might be frequently exposed to the virus leading to a sustained response while those with waning of antibody response may not have encountered the virus after their initial exposure.…”
Section: Discussionsupporting
confidence: 72%
“…Also in murine models, it has been reported that lethal antibody enhancement of dengue disease can be prevented by Fc modification 60 . More recently, severe dengue illness was explained by a substantial production of IgGs with enhanced affinity for the activating Fc receptor FcγRIIIA 61 , whilst another study found higher dengue IgG levels in symptomatic infections compared to asymptomatic ones 62 . Thus, the coefficients retrieved for IgG here might be an indication that children displaying increased IgG tires had high affinity IgGs.…”
Section: Discussionmentioning
confidence: 99%
“…Administration is the weak link of urban integrated mosquito management in the city [42]. To combat mosquito-borne diseases [43,44] and to improve the quality of life of residents, we recommend that PHCS honestly reveals defects in urban mosquito management and seriously takes those exposed defects. The PHCS should strengthen PHC activities by strict adherence to NSC standards.…”
Section: Resultsmentioning
confidence: 99%